Identifying the Constraints Faced by Medical Sciences Universities in Entering the Second Phase of Health Financial Management Reform: A Qualitative Study - peivand bastani; masoud Abolhallaje; Ahmad‌ Sadeghi; Maryam Ramezanian; Hojat‌ Hamidi (Kerman University of Medical Sciences, 2016)
Identifying the Constraints Faced by Medical Sciences Universities in Entering the Second Phase of Health Financial Management Reform: A Qualitative Study Bastani Peivand‌1*, Abolhallaje Masoud‌2, Sadeghi Ahmad‌3, Ramezanian Maryam4, Hamidi Hojat‌5 Received: 16. 09. 2015             Revised: 09. 01. 2016              Accepted: 18. 02. 2016 1. Assistant Professor, Health Management and Human Resources Research Center, School of Management & Medical Information, Shiraz University of Medical Sciences, Shiraz, Iran. 2. Assistant Professor, Budget & Performance Monitoring Center, Ministry of Health & Medical Education, Tehran, Iran. 3. PhDStudent, School of Management & Medical Information, Shiraz University of Medical Sciences, Shiraz, Iran. 4. PhD Student, Health Services Management Research Center, Institute for Futures Studies in Health, Kerman University of Medical Sciences, Kerman, Iran. 5. MSc, Department of Financial Management, Shiraz University of Medical Sciences, Shiraz, Iran. *Correspondence: School of Management and Medical Information, Building Diamond, Alley 29, SadraGhasroldashti Street, Shiraz, Iran. Tel: 071-32340039                               E-mail: bastanip@sums.ac.ir Abstract Introduction:Due to the need for transition from accrual accounting as the first phase of health financial management reform to unit cost as the second phase of this reform, this study was conducted in 2012 to investigate the most important constraints faced by Medical Sciences Universities against this reform. Method:This was a qualitative study throughhapplying Delphi method. Fifteen experts including resource development assistants and financial managers of Medical Universities accompanied with experts in health new financial management reform from Ministry of Health and Medical Education were attended 3 rounds of Delphi for achieving agreement. Results:Findings indicated that the most potential constraint belongs to the "need for human resource empowerment in executive body of the universities". "Novelty of unit cost in health sector" and "lack of previous similar experience" were also identified as the first actual limitations in establishing the second phase of health financial management reform. Conclusion:Considering the complete establishment of accrual accounting as one of the most important pre requisites for unit cost success, in order to flatten the way for reform,it is necessary to prepare a unique and specific framework and guideline for unit cost of services through contribution of all departments and branches of MOHME and financial officers of Universities of Medical Sciences. Keywords: Accrual accounting, Unit cost, Health financial reform, University of Medical Sciences, Delphi technique Citation:Bastani P, Abolhallaje M, Sadeghi A, Ramezania M, Hamidi H.Identifying the Constraints Faced by Medical Sciences Universities in Entering the Second Phase of Health Financial Management Reform: A Qualitative Study. Journal of Health Based Research 2016; 1(3): 189-198.